Investigation of Antibacterial Effects of Electromagnetic Waves Emitted by Mobile Phones - Akbal, Ayhan; Balik, Hasan H. (Hard, 2013)
It is known that antibiotics cause allergies in some people as well as their overdoses inducing kidney and liver failure. They may also cause side effects such as glossitis, stomatitis, nausea, vomiting, pseudomembranous colitis, diarrhea, skin erythema, and dermatitis. In this study, possible antibacterial effects of electromagnetic waves were investigated to find an alternative solution to antibiotics. To investigate antibacterial effects of electromagnetic waves, E. coli and B. subtilis were considered as example organisms. As a result of performed experimental studies, it was shown that electromagnetic waves suppress the growth of microorganisms.
Keywords: antibacterial effect; electromagnetic effect; mobile phone; E. coli; B. subtilis